Making investments in Ho Chi Minh Ville - Nguyen Dinh Nam Tran Anh Tuan; Tran Anh Tuan; Kieu An (Ho Chi Minh City Union of Scientific and Technical Associations of Hochiminh Ville, 1993)
Contents: History and development of Ho Chi Minh ville; industries and handicrafts; agriculture; commerce and service; science and technology in economic development; investments and foreign economic relations in HoChiMinh ville...
Keywords: Tham khảo